EVALUASI MODEL CIPP PADA PROGRAM LITERASI SEKOLAH DI SMP - Ponto, Herlin Pebrianti Yuanita; Rasyid, Muhammad Nur Akbar; Mania, Sitti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to evaluate the implementation of the literacy program at SMP Negeri 2 Parigi using the CIPP Model (Context, Input, Process, Product). This model was chosen for its ability to comprehensively evaluate programs, from the context of program needs, the resources used, the implementation process, to the outcomes achieved. Data were collected through interviews, observations, and documentation involving the school principal, teachers, students, and librarian. Data analysis was conducted qualitatively with triangulation techniques to ensure data validity. The results show that the literacy program at SMP Negeri 2 Parigi is a strategic initiative to enhance students' literacy culture. Context evaluation revealed that the program was designed to address students' low reading interest and improve literacy skills, although integration of literacy into all subjects is still needed. In terms of input, human resources and facilities are available but remain limited, particularly in the collection of books and budget allocation. Process evaluation indicated that the program runs regularly every week with an average participation rate of 75%. However, consistency in implementation and the engagement of students with low literacy skills need improvement. Product evaluation showed significant improvements in reading interest and literacy skills, with 50% of students reaching the